An intercomparison of aerosol absorption measurements conducted during the SEAC4RS campaign. Issue 9 (2nd September 2018) - Mason, B.; Wagner, N. L.; Adler, G.; Andrews, E.; Brock, C. A.; Gordon, T. D.; Lack, D. A.; Perring, A. E.; Richardson, M. S.; Schwarz, J. P.; Shook, M. A.; Thornhill, K. L.; et al.
Abstract: During the SEAC 4 RS campaign in 2013, inflight measurements of light-absorption by aerosol in biomass burning and agriculture fire plumes were collected along with concomitant measurements of aerosol extinction, scattering, and black carbon mass concentration. Here, we compare three measurements of aerosol absorption coefficients: from a photoacoustic spectrometer (PAS), a particle soot absorption photometer (PSAP), and a continuous light absorption photometer (CLAP). Each of these absorption measurements was collected in three visible spectral regions: red, green, and blue (although the precise wavelength and bandwidth vary with each instrument). The absorption measurements were compared during the plumes, in the boundary layer, and in the free troposphere. The slopes from the comparison ranged from 0.6 to 1.24. For biomass burning plumes, the uncertainty in the absorption measurements translates into a range in single scattering albedos of 0.93–0.94 at a wavelength of 660 nm, 0.94–0.95 at 532 nm and 0.92–0.95 at 405 nm. Overall, the aerosol absorption instruments agreed within their stated accuracies. Comparisons with simultaneous measurements of refractive black carbon mass concentration (collected by a single particle soot photometer), were used to derive the mass absorption coefficients (MAC). For all wavelengths, the MAC was high by greater than a factor of three compared to the expected MAC for black carbon. © 2018 American Association for Aerosol Research